Adsorptive removal of phosphate by a Fe–Mn–La tri-metal composite sorbent: Adsorption capacity, influence factors, and mechanism. Issue 7 (October 2020) - Zhu, Yuanrong; Yue, Xianming; Xie, Fazhi
Reducing input of phosphorus is the key step for control of eutrophication and algal blooming in freshwater lakes. Adsorption technology is a cost-effective technology for phosphate removal in water for the purpose. Thus, in this study, a novel Fe–Mn–La tri-metal composite sorbent was developed, and then evaluated for phosphate removal. The results showed that the maximum adsorption capacity could be approached to 61.80 mg g −1 at 25°C under pH of 6.03. Adsorption of phosphate by Fe–Mn–La tri-metal composite adsorbent fitted better by pseudo-second-order kinetic equation and Langmuir model, which suggested that the adsorption process was surface chemical reactions and mainly in a monolayer coverage manner. The thermodynamic study indicated that the adsorption reaction was an endothermic process. The phosphate removal gradually decreased with the increasing of pH from 3.02 to 11.00. The sequence of coexisting anions competing with phosphates was that CO3 2− > Cl − > SO4 2− > NO3 − . Dissolved organic matter, fulvic acid as a representative, would also decrease adsorption capacities of phosphate by Fe–Mn–La tri-metal composite adsorbents. Adsorption capacity would be decreased with increasing addition of adsorbents, while removal efficiency would be increased in this process. The Fe–Mn–La tri-metal composite adsorbent showed a good reusability when applied to removal of dissolved phosphate from aqueous solutions. The Fourier transform infrared spectrometer and X-ray photoelectron spectroscopy analyses indicated that some hydroxyl groups (–OH) on the surface of adsorbent were replaced by the adsorbed PO4 3−, HPO4 2−, or H2 PO4 − . Aggregative results showed that the novel Fe–Mn–La tri-mental composite sorbent is a very promising adsorbent for the removal of phosphate from aqueous solutions.